Iowa Birdline update, March 2, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for March 2, 1992. The highlights for the update include sightings of a Northern Saw-whet Owl, Common Redpolls and a first year Iceland Gull. Also included are handwritten notes with sightings of a Snowy Owl, and a very early Barn Swallow. Epson - sheet feed/flatbed